2005
DOI: 10.1002/adsc.200404313
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of 1,3-Butadiene to 1-Butene by Pd(0) Nanoparticles Embedded in Imidazolium Ionic Liquids

Abstract: The reduction of Pd(acac) 2 (acac ¼ acetylacetonate), dissolved in 1-n-butyl-3-methylimidazolium hexafluorophosphate (BMI · PF 6 ) or tetrafluoroborate (BMI · BF 4 ) ionic liquids, by molecular hydrogen (4 atm) at 75 8C affords stable, nanoscale Pd(0) particles with sizes of 4.9 AE 0.8 nm. Inasmuch as 1,3-butadiene is at least four times more soluble in the BMI · BF 4 than butenes, the selective partial hydrogenation could be performed by Pd(0) nanoparticles embedded in the ionic liquid. Thus, the isolated nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 35 publications
8
142
0
1
Order By: Relevance
“…This result is in agreement with those reported for the hydrogenation of 1,3-butadiene catalysed by metal Pd-NPs in IL. 33 In that case, the difference in solubility between the substrate (1,3-butadiene) and the major product 1-butene plays the role for the observed selectivity (up to 72% in 1-butene). Moreover, no isomerisation process was detected at the different stages of the diene consumption, indicating that the NPs dispersed in IL act as heterogeneous catalysts.…”
Section: Partial Hydrogenation Of Alkynes In Liquid-liquid Biphasic Smentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in agreement with those reported for the hydrogenation of 1,3-butadiene catalysed by metal Pd-NPs in IL. 33 In that case, the difference in solubility between the substrate (1,3-butadiene) and the major product 1-butene plays the role for the observed selectivity (up to 72% in 1-butene). Moreover, no isomerisation process was detected at the different stages of the diene consumption, indicating that the NPs dispersed in IL act as heterogeneous catalysts.…”
Section: Partial Hydrogenation Of Alkynes In Liquid-liquid Biphasic Smentioning
confidence: 99%
“…On the other hand, efficient synthesis of Pd-NPs (diameter: 4.9 nm) from the reduction of Pd(acac) 2 (acac ¼ acetylacetonate) by molecular hydrogen using non-functionalised ILs as unique stabilisers was demonstrated earlier. 33 However, these nanoparticles are not stable and the use of phenanthroline as additional capping agent is essential for the NPs stabilisation. 34 The use of external capping agents, or functionalised ILs such as 2,2 0 -dipyridylamine-functionalised imidazolium salts, 35 polymers 36 or ionic carbon nanotubes 37 have been used for the stabilisation and dispersion of Pd-NPs in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pd 0 nanoparticles in "classical" ILs such as BMI·PF 6 tend to agglomerate after the hydrogenation of alkenes. [26] However, phenanthrolineprotected palladium nanoparticles in this IL are very active and selective for the hydrogenation of olefins, and the nanoparticles/IL system could be reused several times without a loss of activity. [53] Moreover, elegant investigations by Dyson and co-workers on functionalized ILs [85,86] such as imidazolium or pyridinium salts with the nitrile functional group attached to the alkyl side demonstrated that the ILs could act as both solvent and ligand for metal-catalyzed reactions.…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…Indeed, XPS spectra after sputtering displays mainly the M À M component at the 4f region, demonstrating that only the external surface metal atoms are bound to F and O. [24,26,30,33,35] Inasmuch as most of the 1,3-dialkylimidazolium ionic liquids have extremely low vapor pressure [36][37][38] and relatively high viscosity at room temperature, [39][40][41][42] in situ TEM [23,43] and XPS [44] -which require high vacuum-could be performed with the MNPs dispersed in ILs. [37] The size and shape determined by this TEM in situ technique are the same as that obtained with the isolated nanoparticles which were mixed with an epoxy resin distributed between two silicon wafer pieces.…”
Section: Introductionmentioning
confidence: 99%
“…These include typical homogeneous as well as heterogeneous catalytic reactions such as hydrogenation of multiple bonds, Huang et al, 2003;Scheeren et al, 2003;Kim et al, 2004;Silveira et al, 2004;Umpierre et al, 2005;Migowski & Dupont, 2007;Rossi et al, 2007;Scholten et al, 2007;Hu et al, 2008;Prechtl et al, 2008;Gelesky et al, 2009;Hu et al, 2009;Prechtl et al, 2009;Redel et al, 2009;Rossi & Machado, 2009; and carbon-carbon cross-coupling reactions. Pd-based carbon-carbon cross-coupling reactions were discovered more than three decades ago, and remain under the most investigated transition-metal catalysed reactions.…”
Section: Introductionmentioning
confidence: 99%